Evaluating, and Scaling Web Programming Languages: A Comparison between PHP, JavaScript - Mahmood Abdullah (Al-Rafidain Journal of Computer Sciences and Mathematics)
This work concerns with comparing web server resources. The most known web programming languages (PHP-JavaScript) were presented. An age calculator implemented as a web application. Many readings were taken as response time, CPU load and other readings are examined and compared. PHP was found to give best results in some cases and JavaScript is more suitable for other cases.